Impacto de alterações no mercado de trabalho sobre a relação entre contribuintes e beneficiários do Regimento Geral de Previdência Social - Juliana Rodrigues Vieira (2011)
The brazilian population is going through major changes in its age structure. The main change in the brazilian population is the fast increase in the percentage of elderly in the total population. In parallel to this scenario, there are several important changes in the brazilian labor market in recent decades: increasing female labor force participation rates, changes in the participation of the youth and elderly, and high percentage of workers in informal condition.The association of these changes have an important impact on the brazilian public pension system (RGPS), more specifically to the evolution of the number of beneficiaries and contributors to the system and, consequently, to its fiscal equilibrium. In this sense, the main objective of this thesis is to investigate the impact of changes in the brazilian population age structure and labor market on the public pension system. In addition to that, the thesis forecast different scenarios of beneficiaries and contributors taking into account the main changes in the labor market observed in recent decades. The thesis contributes to the literature by showing the importance of considering different labor market scenarios when studying the evolution of the brazilian public pension system. The main result is that the relation between contributors and beneficiaries is expected to decrease significantly over the next decades, meaning a larger number of beneficiaries to taxpayers. The analysis using different scenarios provides an important tool to analyze the situation and prepare different policy to face this situation.